Efek Mediasi Kepuasan Kerja terhadap Kinerja Dosen melalui Pengembangan Karir dan Keadilan Kompensasi - Meta Ika Andrayani; Tatiek Nurhayati; Indarto Indarto (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the influence of career development, compensation equity, and job satisfaction as intervening variables on lecturer performance at College X. The background of this study focuses on low lecturer performance, which is suspected to be influenced by career development, compensation equity, and job satisfaction, key elements in educational organizations that improve lecturer performance. This study uses career development and compensation equity as independent variables, while job satisfaction and lecturer performance served as dependent variables. The sample size was 41 respondents, obtained through a saturated sampling technique. The research method used was quantitative with an explanatory research approach. Data were analyzed using Structural Equational Modeling (SEM) with Partial Least Squares (PLS), using a likert-based data measurement scale. This study found that career development and compensation equity have a positive and significant influence on job satisfaction and lecturer performance. Furthermore, the path test results show that job satisfaction acts as a mediator in the influence of compensation equity on lecturer performance. However, job satisfaction does not mediate the influence of career development on lecturer performance. Universities need to strengthen compensation equity, strengthen career development strategies, implement career development programs, and create a supportive and adequate work environment and facilities to ensure optimal lecturer performance.